The Pandemic, governance and human rights - Figueroa Gutarra, Edwin Vilmer (2021)
The COVID-19 has placed the whole of humanity in a labyrinth, similar to that of the Minotaur, which demands scrutinizing complex exits to overcome the pandemic. Our lives have been radically transformed by the enormous restrictions on fundamental rights in all countries of the world. In this dilemma, it is necessary to reexamine the concept of governance and its various variants concerning public policies, as well as to reassess the axiological dimension of human rights as central elements to be taken into account in the courageous struggle to recover part of our former normality. On this path, the fight against the pandemic has taught us some valuable lessons that should be highlighted.